Առաքել Սյունեցու՝ Տյառնընդառաջի, Ծաղկազարդի, Հարության և Վարդանանց սրբերին նվիրված անտիպ տաղերը - Արաբյան, Արևիկ
Arakʻel Siwnetsʻi’s (14th and 15th centuries) literary legacy is still not comprehensively published, and the authorship of some of his verses remains debatable. In his book Arakʻel Siwnetsʻi and His Poetry, member of the Mechitarist congregation of Venice Mkrtichʻ Poturean has published some of his verses, and discussed in the introduction their authorship and the scant biographical data about Siwnetsʻi. Bibliographer Hakob Anasyan wrote about some published and unpublished odes ascribed to Arakʻel precising Siwnetsʻi’s authorship on the basis of the analysis of their stylistic and metrical characteristics. The article contains a critical edition of some verses ascribed to Arakʻel Siwnetsʻi, based on three manuscripts from Matenadaran. Художественное наследие Аракела Сюнеци (XIV-XV вв.) по сей день издано не полностью, а авторская принадлежность некоторых его стихов остается спорной. Член венецианской конгрегации Мхитаристов Мкртич Потурян в книге «Аракел Сюнеци и его стихи» опубликовал ряд стихов Аракела, обсудив в предисловии их авторскую принадлежность, а также скудные факты жизни Сюнеци. К изданным и неизданным стихотворениям, приписываемых Аракелу, обращался библиограф Акоб Анасян, который уточнил их принадлежность Сюнеци на основе анализа стилистических и метрических особенностей. В статье приводится критический текст приписываемых Аракелу Сюнеци и прежде не изданных стихов, основанный на трех рукописях Матенадарана.
Keywords: Հրապարակումներ; Տաղարան